Engineering a reporter cell line to mimic the high oligomannose presenting surface immunoglobulin of follicular lymphoma B cells - Butaek Lim (Nature Portfolio, 2021)
Abstract Subtypes of B cell non-Hodgkin’s lymphomas, including follicular lymphomas, have shown a unique high oligomannose presentation on their immunoglobulins that will interact with natural receptors of the innate immunity, reportedly causing stimulation and proliferation. From deep sequencing of the variable heavy and light chain sequences of follicular lymphoma involved tissue sections, we identified the consensus variable sequences possessing glycosylation sites at the complementarity determining region. Using this information, we developed a cell line, referred to here as BZ, which displays the consensus variable segments as part of a surface antibody (IgM) and confirmed its presentation of high oligomannose on the heavy chain both in vitro and in vivo. An mCherry expressing variant provided a reporter cell line displaying the high oligomannose surface biomarker while affording clear fluorescent signals for FACS screening as well as for fluorescent in vivo imaging of ectopic xenograft tumors. In developing this reporter cell line that displays the biomarker glycan of follicular lymphoma, we provide a tool that may be used for future screening and validation of receptive moieties for selectively binding high oligomannose for development of targeted diagnostics or therapeutics to such B cell malignancies that display this unique glycan.